The myth of the subclinical rejection: Is it real? - El Essawy, Basset (African Journal of Nephrology, 2009)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Subclinical rejection (SCAR) of renalallografts refers to graft lymphocytic infiltrationtaking acute rejection histologic pattern despitestable renal function. There are no data to suggestthat subclinical tubulointerstitial inflammation isregulatory or in any way beneficial to the graft. Wehave investigated whether C57BL/6 CD8 T cellshome to long term engrafted (LTE) DBA/2 skinallografts and if it is protecting or rejecting. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Methods and results: We transplanted two groupsof B6 CD4 KO mice, 6 mice each, with MHCmismatched DBA/2 skin. Only the 1st group wastreated with Rapamycin (RPM) as reported. After100 days of LTE, we challenged RPM treated hostswith a 2nd DBA/2 skin graft. The 2nd but not the 1stgraft was rejected. Then we investigated thefunctional effects of graft inflitrating CD8 T cells.DBA/2 skin grafts were harvested 100 daysposttransplantation from (i) RPM treated B6 CD4ko mice (N=5) and (ii) skin autografts (N=5) inDBA/2 recipients. LTE DBA/2 allografts or controlDBA/2 autografts were then transplanted ontoC57BL/6-Rag KO hosts, and peripheral bloodlymphocytes (PBL) samples were collected 30 dayspost skin transplantation. CD8T cells can not bedetected in PBL of nae RAG-/- mice. 4.6 % CD8T cells are detected in PBL of RAG-/- recipients ofLTE allografts, but not in recipients of syngeneicgrafts. To test the protective function of the grafthoming CD8 T cells (from LTE RPM mice) thatexpanded by homeostatic proliferation and arepresent in PBL of the RAG-/-, 0.2 x 106 CD8 Tcells from naive CD4KO mice were adoptivelytransferred into the RAG-/- hosts bearing the LTEDBA/2 allografts or DBA/2 autografts 30 daysfollowing skin transplantation. Survival of LTEDBA/2 skin allografts transplanted onto RAG-/-mice were significantly prolonged. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Graft infiltrating CD8 T cells areregulatory and functionally active to protectallograft from rejection.